2020
DOI: 10.1242/jeb.221804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of membrane fatty acid composition on cellular metabolism and oxidative stress in dermal fibroblasts from small and large breed dogs

Abstract: There is ample evidence that cell membrane architecture contributes to metabolism and aging in animals; however, the aspects of this architecture that determine the rate of metabolism and longevity are still being debated. The 'membrane pacemaker' hypothesis of metabolism and of aging, respectively, suggest that increased lipid unsaturation and large amounts of polyunsaturated fatty acids (PUFAs) in cell membranes increase the cellular metabolic rate as well as the vulnerability of the cell to oxidative damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
2
4
0
Order By: Relevance
“…These patterns contrast with the results reported by the Valencak and Ruf (2007) comparative study on mammals, which found no link between BMR and DBI, PUFA, or MUFA and even a negative association of BMR with PI. However, the high level of MUFA in species with low BMR observed in our analysis is in accordance with the recent study in dogs, demonstrating a decrease in cellular metabolic rate following an enrichment of fibroblasts with MUFA (Jimenez et al, 2020). It is important to note, however, that 95% credible intervals of our estimates marginally contained zero, and we performed a high number of comparisons in our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…These patterns contrast with the results reported by the Valencak and Ruf (2007) comparative study on mammals, which found no link between BMR and DBI, PUFA, or MUFA and even a negative association of BMR with PI. However, the high level of MUFA in species with low BMR observed in our analysis is in accordance with the recent study in dogs, demonstrating a decrease in cellular metabolic rate following an enrichment of fibroblasts with MUFA (Jimenez et al, 2020). It is important to note, however, that 95% credible intervals of our estimates marginally contained zero, and we performed a high number of comparisons in our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Higher levels of lipid peroxidation in NMRs seem to not be associated with their membrane peroxidation index (28). Similarly, cell membranes of primary fibroblast cells from small-and large-breed dogs did not show any differences in peroxidation index or saturation levels (26). It is suspected that the higher lipid peroxidation level in NMR comes from an abundance of ROS production during the growing process that is not properly thwarted, and, thus, builds up with age, over time (28).…”
Section: R206mentioning
confidence: 93%
“…We have previously shown circulating lipid damage increases in domestic dogs as they age, and the increases in circulating lipid damage in small breeds compared with large breeds (6). We also know that, at least in primary fibroblast cells isolated from small and large breed dogs, membrane fatty acid composition is not different (27), so that increases in lipid peroxidation rates in domestic dogs may not be stemming from inherent lipid composition differences in their cellular membranes. Taken together, these data imply that AGEs concentrations may be kept at low concentration in domestic dogs across their lifespan, unless pathological states develop; And, that lipid metabolism, rather than carbohydrate metabolism, may be upregulated in domestic dogs to yield the previously found differences in circulating lipid damage across lifespan and body sizes (6) or that any damage associated with AGEs is accumulated through lipid damage rather than glycative stress.…”
Section: Discussionmentioning
confidence: 99%